2021
DOI: 10.3389/fphys.2021.642850
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Cerebrovascular Reactivity MRI in Brain Rehabilitation: A Mechanistic Perspective

Abstract: Cerebrovascular control and its integration with other physiological systems play a key role in the effective maintenance of homeostasis in brain functioning. Maintenance, restoration, and promotion of such a balance are one of the paramount goals of brain rehabilitation and intervention programs. Cerebrovascular reactivity (CVR), an index of cerebrovascular reserve, plays an important role in chemo-regulation of cerebral blood flow. Improved vascular reactivity and cerebral blood flow are important factors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 142 publications
1
6
0
Order By: Relevance
“…Some hypothesize that reduced cerebrovascular reactivity with aging and in individuals post-stroke is due to arterial stiffness and poor vasomotor capability. 44 Our study supports this hypothesis by showing an association between MCAv responsiveness during HIIT and arterial stiffness. Prior studies have also shown that statin use may increase cerebrovascular reactivity to carbon dioxide and the MCAv response to moderate-intensity continuous exercise in individuals post-stroke.…”
Section: Discussionsupporting
confidence: 85%
“…Some hypothesize that reduced cerebrovascular reactivity with aging and in individuals post-stroke is due to arterial stiffness and poor vasomotor capability. 44 Our study supports this hypothesis by showing an association between MCAv responsiveness during HIIT and arterial stiffness. Prior studies have also shown that statin use may increase cerebrovascular reactivity to carbon dioxide and the MCAv response to moderate-intensity continuous exercise in individuals post-stroke.…”
Section: Discussionsupporting
confidence: 85%
“…While CVR is a prominent and common test both clinically and in research, it has varying degrees of predictive value for cerebrovascular risk depending on the population investigated; the literature on CVR in ageing and pathology is rife with between‐study methodological inconsistency making collective interpretation difficult, though CVR certainly seems to be impaired with age and several diseases (Alwatban et al., 2021; Hoiland et al., 2019; Krishnamurthy et al., 2021; Lu et al., 2011; Williams et al., 2021).…”
Section: Cerebrovascular Reactivity In Central Sleep Apnoea and Conge...mentioning
confidence: 99%
“…In recent years, research shows that cerebrovascular control and its integration with other physiological systems (such as cardiovascular and pulmonary) play a key role in improved brain functioning via rehabilitation programs ( 60 ). Aerobic exercise is an important rehabilitation approach that can non-pharmacologically invoke cardiovascular responses that improve cerebrovascular function ( 61 ) (for example, CBF), and neurophysiology ( 62 , 63 ) (i.e., GABA and glutamate).…”
Section: Discussionmentioning
confidence: 99%